Studies on Rice Bran Wax as Modified Pharmaceutical Excipient - Malviya, Rajeev (International Journal of Pharmaceutical & Biological Archive, 2017)
Waxes have been used in many cosmetic preparations and pharmaceuticals as formulation aids. Rice branwax is a byproduct of rice bran oil industry. Present investigation has been aimed to explore the possibleutility of rice bran wax as ointment base compared to standard base. In the pharmaceutical industries,waxes have been employed for different preparation, such as tablet, ointment, emulsion and even inmicro-particles. So study of drug release properties using waxes is far most important. Some waxes likebees wax, carnauba wax, paraffin wax and sugarcane wax etc. are available in the market and is beingused by pharmaceutical industries. Present study attempts to find if rice bran wax is useful as ointmentbase. The oleaginous type ointment bases is prepared by using rice bran wax and evaluated for theirclarity, pH, viscosity, spread ability, skin irritation test in vitro diffusion studies and compared with themarketed formulations. The results obtained in the present study indicate, rice bran wax can be used as agood component in ointment base, comparable with white wax.